2021
DOI: 10.1097/iae.0000000000003210
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Neurosensory Retinal Transplantation

Abstract: Purpose: To review the autologous retinal transplantation surgical technique, indications, rationale, and current outcomes of data published to date.Methods: Review of surgical technique, preoperative and postoperative best-corrected visual acuity, and macular hole (MH) closure rate in studies with at least five eyes.Results: The weighted average macular hole closure rate is 88%, with a MH closure rate ranging from 66.7% to 100%. The weighted average best-corrected visual acuity improved from mean logarithm of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…5 Other series also reported that 74% of patients with macular hole and retinal detachment had an increase in vision of 3 lines or more. 13 In our case, VA was HM before autograft transplantation and increased to 5/100 at the last follow-up at 18 months. Retinal reattachment also contributes to the increase in VA. Postoperative OCT imaging has demonstrated reduced disruption of the EZ, partial restoration of the external limiting membrane, graft integration into the host retina, and varying inner segment EZ visibility.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…5 Other series also reported that 74% of patients with macular hole and retinal detachment had an increase in vision of 3 lines or more. 13 In our case, VA was HM before autograft transplantation and increased to 5/100 at the last follow-up at 18 months. Retinal reattachment also contributes to the increase in VA. Postoperative OCT imaging has demonstrated reduced disruption of the EZ, partial restoration of the external limiting membrane, graft integration into the host retina, and varying inner segment EZ visibility.…”
Section: Discussionmentioning
confidence: 45%
“…The retinal autograft tissue serves as a bridge for the proliferation of glial tissue between the edges of the macular hole. At the same time, Patel et al 13 speculated that this technique may allow for neural tissue replacement in the macular hole through possible ectopic synaptogenesis, retinal progenitor cell differentiation and integration, and/or transfer of progenitor cell material.…”
Section: Discussionmentioning
confidence: 99%
“…Eighty percent of grafts were taken from the superior mid-periphery except in two patients with associated rhegmatogenous retinal detachment, in whom the retinal patch was obtained directly from the edge of a leaking tear. The retinal free flap was transferred to the recipient site to cover or fill the FTMH [ 15 , 22 ]. hAM plug: The plug was shaped from the donor tissue and inserted into the vitreous cavity through a valveless trocar or by temporary removal of the trocar.…”
Section: Methodsmentioning
confidence: 99%
“…Eighty percent of grafts were taken from the superior mid-periphery except in two patients with associated rhegmatogenous retinal detachment, in whom the retinal patch was obtained directly from the edge of a leaking tear. The retinal free flap was transferred to the recipient site to cover or fill the FTMH [ 15 , 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Autologous retinal transplantation (ART) ( Figure 12 ) may be a successful surgical option in patients with a refractory IMH. The theoretical advantage of ART is that the transplanted retina integrates into the adjacent tissue, potentially improving visual recovery compared with other inert tissue scaffolds [ 77 ].…”
Section: Developmentmentioning
confidence: 99%